The Female Sacrifice In Erotic Love In The Novel Lam Yakun Yauman Lahā By Iman Abdul Wahid: A Study Of Erich Fromm’s Psychology - Laeli, Alfil (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes women’s sacrifices in erotic love in the novel Lam Yakun Yauman Lahā by Iman Abdul Wahid using Erich Fromm’s psychological perspective. The study aims to identify the forms of sacrifice made by the character Shireen and interpret their meaning based on the concept of erotic love in The Art of Loving. The method used is descriptive-qualitative with a literary psychology approach. The research data consists of quotations from the novel that demonstrate Shireen’s acts of sacrifice toward Ezzat. The results of the study indicate that Shireen’s sacrifice is manifested through various actions, such as defying her father to preserve her love, enduring a forced marriage to protect Ezzat, asking her best friend to marry Ezzat, continuing to protect Ezzat after a long separation, and saving Ezzat’s daughter without regard for her own safety. These sacrifices reflect Erich Fromm’s concept of love as an active act of giving, protecting, and prioritizing the happiness of the beloved. Additionally, Shireen embodies the elements of care, responsibility, respect, and knowledge within erotic love. This study demonstrates that erotic love in the novel is manifested not only through romantic union but also through sacrifice and a willingness to endure suffering for the sake of the beloved.